Smart City Solutions for Waste Management and Pollution Control - Greeshma C; Gracy Bhadani; Eshwar Prasad; Veena B.R (International Journal of Environmental Noise and Pollution Control, 2025)
Recent trends in the role of artificial intelligence, IoT, and other smart technologies have a critical role toward addressing urban environmental challenges related to air quality and waste management in the context of a smart city. This changes the scope of managing air quality as, with the integration of IoT sensors, big data, and AI, they are able to predict pollution levels through real time monitoring and analysis. These technologies enable governments and stakeholders to come up with strategies aimed at emission reduction, air quality improvement, and addressing climate change. In this regard, smart systems make available hyper-local insights that can assist targeted solutions to manage pollution. On the other hand, solutions powered by AI such as automated sorting systems, predictive analytics, waste to energy systems improve process efficiency. These technologies increase efficiency in waste tracking and collection routes, and recycling processes, and thus decrease the cost of production and promote environmental sustainability. Other advances include smart bins and robotics that help in achieving efficient waste management minimizing the negative effects on the environment and helping achieve the goals of resource recovery and the circular economy. This combination of urban planning along with a rise in populations calls for smart waste management systems. It applies automated processes, up-to-date monitoring, and state of art technologies in recycling in order to attain zero pollution, and in the end, fit into wider goals of sustainability through achieving zero waste targets. This paper underlines the transformative potential of AI and IoT in urban governance, environmental management, and sustainability.
Keywords: Deep Learning; Machine Learning; Sustainability; artificial intelligence; circular economy; data mining; sensors